Uptake of COVID-19 vaccine and associated factors among Health Care Workers at Queen Elizabeth Central Hospital in Malawi: A cross-section study. - Angella Joseph Chikhoza; Wingston Ng'ambi; Alinane Linda Nyondo-Mipando (PLOS Global Public Health)
Globally, the introduction of the Coronavirus Disease of 2019 (COVID-19) vaccine within one year of the pandemic brought doubts to the general population including health professionals. Even though Health Care Workers (HCWs) are at a high risk of contracting and transmitting the coronavirus due to their work, their COVID-19 vaccine uptake is unknown. This study aimed to determine the uptake of the COVID-19 vaccine and identify factors associated with uptake among HCWs at Queen Elizabeth Central Hospital (QECH) in Blantyre, Malawi. We conducted a quantitative cross-sectional study at QECH. HCWs over 18 years, and with at least one year working experience at QECH were recruited using a simple random sampling technique between December 2021 and February 2022. Data were collected on sociodemographic characteristics, medical history, COVID-19 and COVID-19 vaccine perspectives. The study was informed by Behavioral and Social Drivers of COVID-19 Vaccination framework. We computed vaccine uptake as number of HCWs fully vaccinated divided by total number of participants recruited in the study. Bivariate and multivariable logistic regression models were used to identify factors associated with vaccine uptake. Of the 273 HCWs enrolled into the study 71% were fully vaccinated. Gender (Adjusted Odds Ratio (AOR) = 0.54, 95% CI: 0.30-0.96), ownership of medical insurance schemes (AOR = 2.90, 95% CI: 1.36-6.18) and history of vaccine refusal (AOR = 0.29, 95% CI: 0.12-0.70) were significantly related to vaccine uptake. Age and work experience were statistically significant. The level of education, the income of HCWs and occupation did not determine whether HCWs got vaccinated against COVID-19. There was high vaccine uptake among HCWs at QECH. Some risk factors for severe COVID-19 such as advancing in age and work experience are persuasive to COVID-19 vaccination. We recommend intensified COVID-19 vaccination campaigns for subgroups such as young adults and female HCWs.